Influence of Procurement Process on Availability of Essential Drugs in Public Health Facilities in Mombasa County, Kenya - Chikophe, Riziki Mwangolo; Tenambergen, Wanja Mwaura; Kyalo, Caroline Kawila (International Journal of Health Sciences, 2024)
Purpose: Procurement process and practices are crucial components in the successful realization of universal healthcare and in particular the availability of essential drugs. Despite multifaceted efforts and inputs to promote the quality of the procurement process challenges still exists in the availability of essential drugs. This study aimed to establish the influence of procurement planning, supplier selection, procurement financing and needs assessment on availability of essential drugs in the public health facilities in Mombasa County, Kenya. This was a cross-sectional descriptive study design which targeted level 4 and 5 health facilities in Mombasa County. The study target population was 1216 health workers who included medical laboratory personnel, clinical officers and medical officers, nurses, pharmacists and pharmaceutical technologists. The study sample was 301. Methodology: Stratified sampling approach was used to distribute the sample among the cadre and random sampling method was used to select the respondents from each strata. Quantitative data was collected using a structured questionnaire. Findings: The study found that procurement planning, supplier selection, procurement, financing and needs assessment were significant factors in influencing the availability of essential drugs with P<0.05. Unique Contribution to Theory, Policy and Practice: The study recommended that counties conduct a comprehensive and regular need assessment of essential drugs in public health facilities, that they develop a robust procurement planning strategy that aligns with the identified needs and available financing, that there should be a transparent and competitive supplier selection process, and to establish strategic partnerships with international organizations, non-governmental organizations, or donor agencies that are committed to improving healthcare access.